The market turn: from social democracy to market liberalism - Offer, A (University of Oxford, 2017)
Social democracy and market liberalism offered different solutions to the same problem: how to provide for life-cycle dependency. Social democracy makes lateral transfers from producers to dependents by means of progressive taxation. Market liberalism uses financial markets to transfer financial entitlement over time. Social democracy came up against the limits of public expenditure in the 1970s. The 'market turn' from social democracy to market liberalism was enabled by easy credit in the 1980s. Much of this was absorbed into homeownership, which attracted majorities of households (and voters) in the developed world. Early movers did well, but easy credit eventually drove house prices beyond the reach of younger cohorts. Debt service diminished effective demand, which instigated financial instability. Both social democracy and market liberalism are in crisis.